Efficacy of a Dual-ring Wound Protector for Prevention of Surgical Site Infections After Pancreaticoduodenectomy in Patients With Intrabiliary Stents: A Randomized Clinical Trial. Issue 1 (July 2018) - Bressan, Alexsander K.; Aubin, Jean-Michel; Martel, Guillaume; Dixon, Elijah; Bathe, Oliver F.; Sutherland, Francis R.; Balaa, Fady; Mimeault, Richard; Edwards, Janet P.; Grondin, Sean C.; Isherwood, Susan; Lillemoe, Keith D.; et al.
Abstract : Objective: To evaluate the efficacy of a dual-ring wound protector for preventing incisional surgical site infection (SSI) among patients with preoperative biliary stents undergoing pancreaticoduodenectomy (PD). Methods and analysis: This study was a parallel, dual-arm, double-blind randomized controlled trial. Adult patients with a biliary stent undergoing elective PD at 2 tertiary care institutions were included (February 2013 to May 2016). Patients were randomly assigned to receive a surgical dual-ring wound protector or no wound protector, and also the current standard of care. The main outcome measure was incisional SSI, as defined by the Centers for Disease Control and Prevention criteria, within 30 days of the index operation. Results: A total of 107 patients were recruited (mean age 67.2 years; standard deviation 12.9; 65% male). No significant differences were identified between the intervention and control groups (age, sex, body mass index, preoperative comorbidities, American Society of Anesthesiologists class, prestent cholangitis). There was a significant reduction in the incidence of incisional SSI in the wound protector group (21.1% vs 44.0%; relative risk reduction 52%; P = 0.010). Patients with completed PD also displayed a decrease in incisional SSI with use of the wound protector compared with those palliated surgically (27.3% vs 48.7%; P = 0.04). Multivariate analysis did not identify any significant modifying factor relationships (estimated blood loss, duration of surgery, hospital site, etc.) ( P > 0.05). Conclusion: Among adult patients with intrabiliary stents, the use of a dual-ring wound protector during PD significantly reduces the risk of incisional SSI.